Evaluation of CETP activity in vivo under non-steady-state conditions: influence of anacetrapib on HDL-TG flux[S] - McLaren, David G.; Previs, Stephen F.; Phair, Robert D.; Stout, Steven J.; Xie, Dan; Chen, Ying; Salituro, Gino M.; Xu, Suoyu S.; Castro-Perez, Jose M.; Opiteck, Gregory J.; Akinsanya, Karen O.; Cleary, Michele A.; et al. (Journal of lipid research, 2016)
Studies in lipoprotein kinetics almost exclusively rely on steady-state approaches to modeling. Herein, we have used a non-steady-state experimental design to examine the role of cholesteryl ester transfer protein (CETP) in mediating HDL-TG flux in vivo in rhesus macaques, and therefore, we developed an alternative strategy to model the data. Two isotopomers ([2H11] and [13C18]) of oleic acid were administered (orally and intravenously, respectively) to serve as precursors for labeling TGs in apoB-containing lipoproteins. The flux of a specific TG (52:2) from these donor lipoproteins to HDL was used as the measure of CETP activity; calculations are also presented to estimate total HDL-TG flux. Based on our data, we estimate that the peak total postprandial TG flux to HDL via CETP is ∼13 mg·h−1·kg−1 and show that this transfer was inhibited by 97% following anacetrapib treatment. Collectively, these data demonstrate that HDL TG flux can be used as a measure of CETP activity in vivo. The fact that the donor lipoproteins can be labeled in situ using well-established stable isotope tracer techniques suggests ways to measure this activity for native lipoproteins in free-living subjects under any physiological conditions.